Squares in Cycles: Prediction of G-Quadruplexes in Circular RNA Secondary Stuctures - Lorenz, Ronny; Stadler, Peter F. (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2024: Anais do XVII Simpósio Brasileiro de BioinformáticaDO - 10.5753/bsb.2024.245308, 2024)
RNA secondary structures, determined by non-crossing base pairs, capture many of the salient features of RNA molecules, explain the free energy of structure formation very accurately, and can be computed efficiently given the sequence information only. G-quadruplexes are compact local structures that have been shown to have important biological function and can be integrated into secondary structure prediction. In recent years circular RNAs have gained considerable interest as a biological relevant subclass of RNAs. While algorithms and tools are available that extend secondary structure prediction from linear to circular RNAs, no support is provided for G-quadruplexes. In this contribution we close this gap and describe how the ViennaRNA package has been extended to include this increasingly relevant case.